EVOLUTIONARY CYCLE OF CYDALIMA PERSPECTALIS WALK. UNDER THE INFLUENCE OF CLIMATE CONDITIONS IN CRAIOVA AREA - Raluca STAN; Ion MITREA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the paper is to highlight the link between climatic conditions and the developmental stages of the species Cydalima perspectalis. If the temperature is low the evolution in days of the development stages increase and vice versa. For the population studied in 2020, the first flight of adults took place on May 18, and the last on October 14. It is clear that it completed 2 generations and the amount of effective temperature for the first generation is 646.7°C and for the second generation it was 628.3°C. The amount of effective temperature (degrees-days)in the period 2019-2020 for the egg stage varies between 62.8°C in 2020 and 48.6°C in 2019, for the larval stage is between 444.8°C (2020) and 403.4°C (2019) and for the pupae stage the values are between 139.1°C (2020) and 74.1°C (2019).Under the natural influence of climatic factors, the number of generations of the species Cydalima perspectalis in the Craiova area varies from one year to another, this suggests that this species is directly dependent on temperature.